Complementizer deletion and the split hypothesis - Elena Isolani (Isogloss)
In Italian and Italo-Romance, the omission of the complementizer takes (at least) three distinct forms: CD1, observable in standard Italian, and CD2 and CD3 available in two Tuscan varieties, respectively in Florentine and Pisano. Although different conditions regarding the main and the embedded verbs independently influence the occurrence of these CD types, they consistently stem from verb movement towards the left-periphery. Resting on this assumption, this article proposes the split hypothesis according to which the verb raises towards distinct left-peripheral projections depending on a bundle of features associated with the main verb’s status and the embedded verb’s modality. Consequently, different types of complementizer deletion are structurally realized in separate projections. Additionally, this article addresses the implicational relation among CD1, CD2 and CD3 providing a theoretical framework rooted in the long-standing locality principle, the Head-Movement Constraint, and offering a parametric analysis via the Parametric Comparison Method, that accounts for the implicational nature of these phenomena.